INVESTIGATION OF THE CURRENT SITUATION OF CLASSROOM TEACHING AND THE NEEDS OF ONLINE MEDIA TEACHING IN HIGHER VOCATIONAL COLLEGES IN CHINA - Wang Zixuan; Yusmarwati Yusof (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Classroom teaching is an important way of practical teaching. In today’s diversified education, classroom teaching is still the basic form of teaching. The purpose of this study is to investigate the current situation of classroom teaching methods in China’s higher vocational colleges, and to analyze students’ satisfaction with the existing teaching methods and the feasibility of reform. A questionnaire was used to collect data. The analysis results show that the current classroom teaching in China’s higher vocational colleges is mainly based on traditional teaching methods, but the students are generally dissatisfied with it, thinking that the teaching method is single, lacks interaction and diversity. However, students have a certain understanding of online media pedagogy and have the foundation of using online media for learning, which provides a good prerequisite for teaching reform. The conclusion of the study is that it is inevitable to reform the traditional classroom teaching method, and the introduction of online media teaching method can effectively improve the classroom interaction and students’ enthusiasm, so as to improve the teaching effect and meet the needs of modern education development.